Pertumbuhan, Produktivitas dan Hasil Hablur Klon Tebu Masak Awal-Tengah di Tanah Inceptisol - ,, supriyadi; Khuluq, Ahmad Dhiaul; Djumali, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2018)
Sugar cane is a strategic commodity for the Indonesian government as raw material for the national sugar industry. Cultivation of sugar cane has been shifted to dry areas dominated by Inceptisol, Vertisol, and Ultisol soil. These conditions require certain clones to obtain high sugar yield. New improved varieties have been developed and 8 early-mid maturiting clones have been obtained. The study was aimed to evaluate and obtain earty-mid maturing clones with higher sugar yield than the existing varieties in dry land of Inceptisol soil. The study was conducted at the Karangploso Experimental Station, Malang from July 2015 to September 2016. The study was arranged in a randomized block design with three replications. The treatment consistsed of eight clones of early to mid maturing sugarcane clones and one control variety (Kenthung). The eight clones were (1) PS 04 117, (2) PS 04 259, (3) PS 04 129, (4) PS 05 258, (5) PS 06 391, (6) PS 06 370, (7) PS 06 188, and (8) JR 01. The results showed that three clones (PS 06 188, PS 05 258 and JR 01) produced higher sugar yield (10.45-11.88 ton ha-1), and the other clones showewd lower sugar yield (6.55-9.37 ton ha-1) than that of Kenthung variety (9.16 ton ha-1).PS 06 188 and PS 05 258 clones obtained the highest sugar yield of 11.88 and 11.49 ton ha-1, respectively.